Sosialisasi Pencegahan Pelecehan Seksual, Bullying Bullying , serta Narkotika di SMP Negeri 3 Meulaboh, Kabupaten Aceh Barat - Omalia, Noka; Mansyur, Alfi; Rehan, Rehan; Rauzah, Rauzah; Irawan, Agus (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This socialization was carried out in one of junior high school namely SMP Negeri 3 Meulaboh. This activity aims to improve and add insight to the younger generation or adolescents regarding the dangers of sexual harassment, drug abuse, and bullying crimes that can occur in today’s school environment. The method used is in the form of presentations related to prevention of sexual harassment, bullying and narcotics. This socialization seeks to prevent the occurrence of bad behavior for the younger generation who are in a period of physical and mental growth and development. The result obtained from this socialization are that students begin to understand the dangers of drugs, sexual harrassment and bullying for the younger generation, and they also begin to know about how to prevent this behavior.